The impact of age, gender, and ocular parameters on corneal biomechanics in Chinese refractive candidates - Jiliang Ning; Siyu Sun; Taorui Yu; Xiaoyu Liu; Lin Jin; Lijun Zhang (PLoS ONE, 2025)
We aimed to quantify the distribution of corneal biomechanics in healthy, myopic Chinese candidates for refractive surgery using an ocular response analyzer, and explore factors that influence corneal biomechanics. In this retrospective cross-sectional study, 1,090 eyes from 1090 myopic patients scheduled for refractive surgery at the Refractive Center of Dalian Third People’s Hospital between January 2021 and May 2022 were examined. Participants were categorized into three groups based on spherical equivalent power: low myopia (SE> −3.00D), moderate myopia (>−6.00D < SE ≤ −3.00D), and high myopia (SE ≤ −6.00D); then further categorized by central corneal thickness into four groups: < 500μm, 500 to <550μm, 550 to <600μm, and ≥600μm. The Ocular Response Analyzer was used to measure corneal hysteresis (CH) and corneal resistance factor (CRF). Differences in CH and CRF were compared across groups. Generalized estimating equations were applied to determine correlations between CH and CRF and variables such as sex, age, corneal keratometry, central corneal thickness, white-to-white corneal diameter, and spherical equivalent power. The average corneal hysteresis (CH) was 11.18 ± 1.35 mmHg, while the average corneal resistance factor (CRF) was 11.22 ± 1.64 mmHg. The average CRF values were significantly higher in men than in women (P < 0.05). In the high myopia group, CH values were significantly lower than those in the moderate and low myopia groups (P < 0.01). CH and CRF increased with corneal thickness across all groups, with statistically significant differences (P < 0.01). Generalized estimating equations showed a positive correlation between corneal thickness and curvature with both CH and CRF (all P < 0.01). Age was negative correlation between CH and CRF (all P < 0.05). Spherical equivalent power was positively correlated with CH (P < 0.01). Corneal thickness, curvature, and refractive power significantly affected corneal measurement values in individuals with myopia. The CH and CRF values increased with increasing corneal thickness and curvature, and CH was negatively correlated with the severity of myopia.